The first law of thermodynamics analysis of transporters involved in the glutamate/gaba-glutamine cycle - Gür, Mert; Yılmaz, Sema Zeynep; Taka, Elhan (Turk Isi Bilimi Ve Teknigi Dernegi, 2021)
The glutamine–glutamate/GABA cycle (GGC) is a sequence of events that provides replenishment of the neurotransmitter pool of glutamate in order to maintain neurotransmitter homeostasis. In the GGC, glutamate or GABA molecules are released from neurons and subsequently taken up into astrocytes. Astrocytes convert glutamate or GABA molecules into glutamine and release them into the synapse. Glutamine molecules are taken up by neurons to be used as a precursor for the synthesis of glutamate or GABA. The transport of these molecules across the membranes of neurons and astrocytes is facilitated by transporter proteins. Each of these transporter proteins is a biomolecular machine; they operate on thermodynamic cycles and convert part of the supplied energy input into useful work output. Energy harnessed from the translocation of molecules/ions down their electrochemical gradient is converted into mechanical useful work translocating molecules/ions against their electrochemical gradient. Conservation of energy principle was applied and thermodynamic first law efficiencies, showing how much of the energy input per cycle is converted into useful work, were evaluated for the thermodynamic cycles of EAAT, ASCT2, B0AT2, SA, SN, and GABA transporters involved in the GGC. Neurotransmitter concentrations in the synapse change upon signal arrival and subsequently return to resting levels, causing transporters to operate under various first law efficiencies. Range of first law efficiencies for EAAT (for glutamate transport), ASCT2, B0AT2, SA SN, GABA (forward mode) were calculated as 60-85%, 46-78%, 61-89%, 61-89%, 55-80%, and 54-76%, respectively. Efficiency values obtained for these transporters are much higher than those of the macro-scaled heat engines we encounter in our daily lives. Furthermore, EAAT showed larger thermodynamic first law efficiency for glutamate transport than aspartate transport, which takes place with a maximum efficiency of 45%. Thus, suggesting the possibility that transport of different substrates by the same transporter may take place with different efficiencies.